SUSTAINABILITY REPORTING, AUDIT QUALITY, LIQUIDITY ON GOING CONCERN AUDIT OPINION WITH GCG AS A MODERATOR : STUDY OF THE UK - Tanggor Sihombing; Stephany Setiadi Putri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This research delves into examining the impact of sustainability reporting, audit quality, and liquidity on going-concern audit opinions, with good corporate governance as a moderating variable. Employing logistic regression analysis using STATA 17, the study analyzed a sample of 220 infrastructure companies in the United Kingdom within period 2019 to 2023. Data samples were collected through purposive sampling from sustainability reports, financial statements, and companies’ annual reports. Findings indicate a negative relationship between sustainability reporting, audit quality, and liquidity on the issuance of going concern audit opinions. These variables do not directly influence auditors' decisions regarding going concern opinions. Moreover, good corporate governance moderates the negative relationship between liquidity and going concern audit opinions. This study contributes to a deeper understanding of the relationship between sustainability reporting, audit quality, and liquidity in the context of going-concern audit opinions, offering valuable insights for both audit practice and academic research.